2016
DOI: 10.7883/yoken.jjid.2015.346
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Shiga Toxin-Producing <i>Escherichia coli</i> Isolated from Humans between 2011 and 2014

Abstract: SUMMARY: Although E. coli O157:H7 is the major serotype among Shiga toxin-producing Escherichia coli (STEC) strains, non-O157 serotypes have caused numerous outbreaks worldwide. We aimed to evaluate the distribution of serogroups, serotypes, virulence genes, and antimicrobial resistance of STEC strains recovered from stool samples. A total of 395 stool samples characterized by watery/bloody diarrhea and/or symptoms of hemolytic-uremic syndrome were included in this study. Strains compatible with E. coli, based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…National Reference Laboratory at Ankara, Turkey, found that 62.5% of the non-O157 STEC isolates were resistant to at least one antibiotic (Gulesen, Levent, Demir, Akgeyik, & Kuran, 2016 The reason for this difference in prevalence of AR-STEC is not known but these studies suggest that there is a prevalence of resistance among STEC isolates from both animal and human sources. (Naseer, Lobersli, Hindrum, Bruvik, & Brandal, 2017).…”
Section: Analysis Of the Clinical (Human) Stec Isolates Collected By Thementioning
confidence: 96%
See 1 more Smart Citation
“…National Reference Laboratory at Ankara, Turkey, found that 62.5% of the non-O157 STEC isolates were resistant to at least one antibiotic (Gulesen, Levent, Demir, Akgeyik, & Kuran, 2016 The reason for this difference in prevalence of AR-STEC is not known but these studies suggest that there is a prevalence of resistance among STEC isolates from both animal and human sources. (Naseer, Lobersli, Hindrum, Bruvik, & Brandal, 2017).…”
Section: Analysis Of the Clinical (Human) Stec Isolates Collected By Thementioning
confidence: 96%
“…Analysis of the clinical (human) STEC isolates collected by the National Reference Laboratory at Ankara, Turkey, found that 62.5% of the non‐O157 STEC isolates were resistant to at least one antibiotic (Gulesen, Levent, Demir, Akgeyik, & Kuran, ). A study in the United Kingdom identified resistance to ampicillin, streptomycin, sulphonamide and tetracycline among the STEC isolates recovered from patients with diarrhoea (81/430; 18%; Day et al, ).…”
Section: Prevalence Of Ar‐stec In Animal Produce and Clinical Sourcesmentioning
confidence: 99%
“…A similar report from the UK reported a prevalence of genotypic resistance as 27.3 % in non-O157 and 17.4 % in O157 strains [18,25]. A higher prevalence of AMR in non-O157 STEC than in O157 STEC has also been reported from various phenotypic studies [19,20,32]. Also, we observed a higher percentage of MDR among the non-O157 strains compared to O157 STEC (8.8 and 7 %), although this was not significant.…”
Section: Discussionmentioning
confidence: 99%